Master of the Universe - Bauder, Marc (Germany : Bauder, Marc ; Glaser, Markus, 2013)
On a vacant floor of a Frankfurt bank building, a former investment banker, Rainer Voss, talks openly about the hypnotic daily practices of financial services, which would sometimes earn him millions of dollars in a single day. Few questions were asked and the opportunities were limitless in capitalism’s golden decade of the 1980's which meant that Voss and other young traders could rise to new heights. Now 50 and unemployed, he strolls, somewhat timidly, around the deserted trading floor and empty conference rooms. He looks back on those days of megalomania when he was a master of the universe with eight monitors and a button to click which could impact events on the other side of the world. But his “ universe” became increasingly obscure, the consequences increasingly unpredictable and in the end the bubble burst. In addition to his personal stories, Voss sheds light on the current economic situation in Europe and explains why banks are unlikely to change course or operate transparently.
Verzio Film Festival Submission
Verzio Film Festival Submission